Soil seed bank characteristics along a gradient of past human disturbances in a tropical semi-deciduous forest: Insights for forest management - Adjalla, Christian; Tosso, Felicien; SALAKO, Kolawolé Valère; ASSOGBADJO, ACHILLE EPHREM (My University, 2022)
The soil seed bank (SSB) in forests is a key indicator of their resilience after disturbances. Despite the growing interest in describing patterns of SSB and understanding potential processes underpinning those patterns, we still know little about SSB patterns and drivers in semi-deciduous tropical forests. Using the regeneration emergence method, we assessed the patterns of SSB (i) across four vegetation types with variable intensity of past human disturbances: typical dense forest - degraded dense forest - young preforest fallow - old preforest fallow, and (ii) in relationships to soil depth (0–5 cm, 5–10 cm, 10–15 cm, 15–20 cm) in a protected tropical semi-deciduous dense forest in Benin, West-Africa. The standing vegetation (adults and regeneration) data and soil samples were collected using a systematic sampling of 60 plots of 10 m × 10 m in the four vegetation types. Herbaceous plants dominated (67% − 78%) the SSB. From the SSB, five tree species emerged: Ceiba pentandra (L.) Gaertn., Dialium guineense Willd., Ficus sur Forssk., Leucaena leucocephala (Lam.) De Wit, and Lonchocarpus sericeus (Poir.) Kunth. Regarding tree species, the total densities of germinated seeds (seeds.m−2) were higher in typical dense forest (28.00 ± 7.22) and young preforest fallow (16.67 ± 7.07) than in old preforest fallow (10.00 ± 6.75) and degraded dense forest (8.89 ± 3.81). When only tree species were considered, the SSB was more diverse and dense in typical dense forest than in other vegetation types suggesting negative effect of past human disturbances on SSB. The similarity of the species composition between the SSB and the surrounding vegetation was low (Jaccard's similarity index ranged from 0 to 17.64%, indicating that the majority of tree species in the surrounding vegetation were absent in the SSB. This study highlighted a need of planting effort of native tree species to restore degraded areas.
Keywords: Soil seed bank; Floristic similarity; Regeneration; Density; Diversity; Western Africa